Governance Quality, Public Health, Education, and Innovation: Study for Novel Implications - Wu, Ning (Frontiers in Public Health, 2022)
Pandemic or worldwide disease is the greatest issue of all time, that not only affects human health but also influences the economic, educational, and other activities of the countries. Since malaria is among the leading health disease that disrupts the economic system of the country. Therefore, the current study aims to analyze whether educational expenditure (EDU) and technological innovation (TI) influences malaria incidence (MI) in emerging economies. This study also examines the role of government effectiveness (GEF), government health expenditure (GHE), gross domestic growth (GDP), human capital (HC), and research and development (R&D) during the period 2000-2018. Employing panel data approaches, including the slope heterogeneity and cross-section dependence, the second-generation unit root test reveals the stationarity of all variables. The study also validates the existence of a long-run relationship between the variables. Based on the asymmetrical distribution properties, this study employed the quantile regression approach. The empirical results asserted that EDU and TI significantly reduce MI in the panel economies. Also, GEF, R&D, and HC adversely affect incidences of malaria. In contrast, GDP is the only factor found that increases MI during the selected period. Based on the empirical results, this study suggested policy measures that could benefit the governors, policy-makers, and scholars.